National security vs. civil & privacy rights - Issitt, Micah L. (Opinions throughout history., 2018)
"This volume offers a sweeping overview of the shifting tensions and public opinions fueled by Americans' expectations of privacy vs. their collective desire for national security. ... Diving into how far the government has gone and "should" go in the name of national security, this volume analyzes primary and secondary source documents such as Supreme Court decisions, articles from respected periodicals, and legislation. Coverage includes domestic spying, Apple's refusal to help with "back door" access of the iPhone, and the differences between President Obama's and President Trump's surveillance states."--Publisher description